Ceria nanoparticles as promoters of CO2 electroreduction on Ni/YSZ: An efficient preparation strategy and insights into the catalytic promotion mechanism. (October 2022) - Chen, Dingkai; Barreau, Mathias; Turczyniak-Surdacka, Sylwia; Sobczak, Kamil; Strawski, Marcin; Salle, Annie Le Gal La; Efimenko, Anna; Teschner, Detre; Petit, Corinne; Zafeiratos, Spyridon
Abstract: Since many decades nickel yttria-stabilized zirconia cermet (Ni/YSZ) has been the most frequently used fuel electrode material for high temperature solid oxide cells (SOCs). However, in recent years there has been considerable effort to improve the Ni/YSZ performance through surface engineering. In this work, we report a simple strategy to apply nanosized un-doped (CeOx ) and Ni-doped (NiCeOy ) ceria particles into porous Ni/YSZ cermet electrodes via infiltration from hexane solution. Detailed characterization of the particles in their solution revealed differences in the ease of agglomeration, with NiCeOy nanoparticles being better dispersed and thus forming smaller aggregates. This property is critical for the effectiveness of the solution in filling the pores of Ni/YSZ cermet and the consequent ceria deposition. In particular, morphological and microstructural characterization reveals that NiCeOy nanoparticles decorate uniformly the pores of Ni/YSZ backbone, deep up to the interface with the electrolyte. More importantly, this can be done with relatively high ceria loading per infiltration/co-firing step. Electrochemical tests demonstrate that infiltrated Ni/YSZ fuel electrodes have improved I-V performance in CO2 electrolysis as compared to pristine Ni/YSZ. Synchrotron-based operando NAP-XPS experiments using both soft and tender X-rays revealed the formation of an ultrathin Ni-Ce 3+ layer on the electrode surface, which can rationalize the ameliorated CO2 electrolysis performance. Graphical Abstract: A simple infiltration strategy to engineer pre-fabricated Ni/YSZ cermet electrodes that promote CO2 electroreduction over solid oxide electrolysis cells via an ultrathin surface layer composed of metallic Ni and Ce 3+ ions. ga1 Highlights: Infiltration of Ni/YSZ cermet with hexane solution containing ceria nanoparticles. Significant ceria loadings are achieved after a single infiltration/co-firing step. Infiltration of Ni/YSZ with ceria improves the I-V curves of CO2 electrolysis. The ceria promotion mechanism is explained by operando NAP-XPS analysis.